Synthesis and enhanced electrochemical supercapacitive properties of manganese oxide nanoflake electrodes. (1st April 2015) - Inamdar, A.I.; Jo, Y.; Kim, J.; Han, J.; Pawar, S.M.; Kalubarme, R.S.; Park, C.J.; Hong, J.P.; Park, Y.S.; Jung, W.; Kim, H.; Im, Hyunsik
Abstract: MnO2+δ (Manganese oxide) nanoflakes were synthesized for use as electrode material in electrochemical supercapacitors. The nanoflakes were produced via RF-magnetron sputtering with various excess oxygen contents (δ), and the electrochemical supercapacitive properties of the MnO2+δ nanoflakes were investigated as a function of δ with the use of a Na2 SO4 electrolyte. The excess oxygen (δ) induces the MnO2+δ nanoflakes to form a thin open structure, and μ-Raman measurements revealed that the MnO2+δ nanoflakes formed a birnessite phase with a layered structure. X-ray photoelectron spectroscopy was used to obtain quantitative information on both the oxidation state and the chemical composition of the nanoflake electrodes. The crystallinity of the nanoflakes improved when the oxygen partial pressure increased during sputtering. At an optimal δ ∼ 0.6, the electrochemical stability and the capacity retention significantly improved, and electrochemical impedance spectroscopy revealed that easy access of Na + ions into the nanoflakes at an optimal δ value resulted in a low diffusion resistance, playing a key role in determining the improvement in the supercapacitor characteristics. Highlights: MnO2+δ nanoflakes are grown using RF-magnetron sputtering. Excess oxygen (δ) endorses the formation of a porous and open structure. At δ ∼ 0.6, the stability and capacity retention are significantly improved. Low diffusion resistance plays a key role in determining supercapacitor characteristics.